Adaptation of flatbed dryer for paddy drying in the Southeast Asian countries - CGIAR Research Program on Rice (2019)
The flatbed dryer is already comercialized in the Southeast Asian countries. This technology is used for drying more than 45, 10, 10, and 5% in Vietnam, Cambodia, Philippines, and Myanmar, respectively.